Bioethics and superior education in Mexico - Cantú Martínez, Pedro César (Acta Bioethica, 2015)
This article refers to the bioethics status in Mexico, characterizing the circumstances and the social context in which it is imparted in institutions of superior education. The development of training programs in this level and continuous education in bioethics topics have become a necessity in order to respond to social demands through training human resources which contribute to enhance society.